Opioidergic, adrenergic and GABAergic modulation of growth hormone and cortisol secretion: A review - Phogat, J B; Rose, M K (The Indian Journal of Animal Sciences, 2012)
Growth hormone (GH) and cortisol are the major metabolic hormones having multiple functions controlling almost every organ system of the body in laboratory and domestic animals. Basically, the release of adenohypophyseal growth hormone is regulated positively and negatively by 2 central neurohormones, growth hormone-releasing hormone (GHRH) and somatostatin, respectively. Similarly, the activity of hypothalamo-pituitary-adrenal axis is mainly under the control of hypothalamic corticotrophin-releasing hormone (CRH) and argenine vasopressin which subsequently regulate the adrenocorticotropin hormone (ACTH) from pituitary and cortisol from adrenal gland. In the recent past, literature has revealed the classical hypothalamic regulation of these 2 hormones involving many other neurogenic and humoral factors. These factors involve sequential events acting through opiodergic, adrenergic and GABAergic mechanisms. However, the effect of these neurotransmitters in modulation of GH and cortisol secretion varies with site of action of these neuropeptides and species involved, and is greatly influenced by age, sex and physiological status of an individual.